Colour theory: advanced approaches and applications - Cairns, Hunter (My University, 2025)
The scope of this project aims to expand knowledge of colour theory learned in the design program and its application in design thinking. This research publication aims to refine the theoretical knowledge of colour theory and expand into reality-based rendering through the influence and interaction of environments. With this knowledge, we can explore how to use colour as a tool to shape perceptions of reality, advancing storytelling methods that go beyond mere illustrative techniques and move into conceptual design thinking. The publication aims to highlight advanced theories, broken down through the lens of student considerations, and paired with the culmination of my personal creative works developed during my time in the undergraduate program.
Presented on December 11, 2025, as a final course presentation to Robert Andruchow, Chair of the Department of Design, at MacEwan University in Edmonton, Alberta.
Keywords: colour theory; design thinking